Pomiar i ocena działalności ośrodków odpowiedzialności w wielonarodowym działającym w branży spożywcze - Makowska, Ewa (Measurement and performance evaluation of the responsibility centres in a multinational enterprise operating in foodstuffs production sector, 2008)
The main objective of this paper is the presentation of financial and non-financial measures are used to determine the performance of responsibility centres in the surveyed multinational enterprises. Various types of responsibility centres have different levels of freedom in choosing the methods and means leading to the completion of assigned objectives. Selected results of the carried out survey research are presented in this paper.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 278-288